Virus-Encoded MicroRNAs Facilitate Gammaherpesvirus Latency and Pathogenesis In Vivo - Emily R. Feldman (American Society for Microbiology, 2014)
ABSTRACT Gammaherpesviruses, including Epstein-Barr virus (EBV), Kaposi sarcoma-associated herpesvirus (KSHV, or HHV-8), and murine gammaherpesvirus 68 (MHV68, γHV68, or MuHV-4), are B cell-tropic pathogens that each encode at least 12 microRNAs (miRNAs). It is predicted that these regulatory RNAs facilitate infection by suppressing host target genes involved in a wide range of key cellular pathways. However, the precise contribution that gammaherpesvirus miRNAs make to viral life cycle and pathogenesis in vivo is unknown. MHV68 infection of mice provides a highly useful system to dissect the function of specific viral elements in the context of both asymptomatic infection and disease. Here, we report (i) analysis of in vitro and in vivo MHV68 miRNA expression, (ii) generation of an MHV68 miRNA mutant with reduced expression of all 14 pre-miRNA stem-loops, and (iii) comprehensive phenotypic characterization of the miRNA mutant virus in vivo. The profile of MHV68 miRNAs detected in infected cell lines varied with cell type and did not fully recapitulate the profile from cells latently infected in vivo. The miRNA mutant virus, MHV68.Zt6, underwent normal lytic replication in vitro and in vivo, demonstrating that the MHV68 miRNAs are dispensable for acute replication. During chronic infection, MHV68.Zt6 was attenuated for latency establishment, including a specific defect in memory B cells. Finally, MHV68.Zt6 displayed a striking attenuation in the development of lethal pneumonia in mice deficient in IFN-γ. These data indicate that the MHV68 miRNAs may facilitate virus-driven maturation of infected B cells and implicate the miRNAs as a critical determinant of gammaherpesvirus-associated disease. IMPORTANCE Gammaherpesviruses such as EBV and KSHV are widespread pathogens that establish lifelong infections and are associated with the development of numerous types of diseases, including cancer. Gammaherpesviruses encode many small noncoding RNAs called microRNAs (miRNAs). It is predicted that gammaherpesvirus miRNAs facilitate infection and disease by suppressing host target transcripts involved in a wide range of key cellular pathways; however, the precise contribution that these regulatory RNAs make to in vivo virus infection and pathogenesis is unknown. Here, we generated a mutated form of murine gammaherpesvirus (MHV68) to dissect the function of gammaherpesvirus miRNAs in vivo. We demonstrate that the MHV68 miRNAs were dispensable for short-term virus replication but were important for establishment of lifelong infection in the key virus reservoir of memory B cells. Moreover, the MHV68 miRNAs were essential for the development of virus-associated pneumonia, implicating them as a critical component of gammaherpesvirus-associated disease.